Epigenetic modifications in developmental coordination disorder: association between DNA methylation and motor performance - Huang, Fangfang; Li, Huizhen; You, Haizhen; Su, Yuantao; Peng, Huijuan; Du, Wenchong; Hua, Jing (Frontiers in Cell and Developmental Biology, 2025)
ObjectiveDevelopmental Coordination Disorder (DCD) is a common neurodevelopmental condition characterized by impaired motor coordination. However, the biological mechanisms underlying DCD remain largely unclear. This study aimed to investigate the potential role of DNA methylation in the pathogenesis of DCD.MethodsGenome-wide DNA methylation analysis was conducted using peripheral blood samples from children with and without DCD. Forty-two key differentially methylated probes (DMPs) were selected for targeted validation using MethylTarget™ sequencing.ResultsA total of 416 DMPs were detected. Using the Bumphunter and ProbeLasso algorithms, 48 and 22 differentially methylated regions (DMRs) were identified, respectively. Among the key DMPs, methylation levels at cg18187326 (FAM45A) and cg11968956 (FAM184A) were significantly associated with both total motor and gross motor scores. In addition, cg03597174 (SEZ6) was negatively associated, while cg05986449 (GPD2) was positively associated with gross motor function.ConclusionThese findings provide preliminary evidence that specific DNA methylation alterations may influence early motor development and potentially contribute to the pathogenesis of DCD. DNA methylation markers may serve as novel biomarkers for early diagnosis and targeted intervention in children with DCD.